Pengaruh Perendaman dan Pemupukan N terhadap Pertumbuhan dan Produksi Padi Toleran Rendaman - Ikhwani Ikhwani (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Ikhwani, 2012. The Effect of Submergence and N fertilizer Application on Plant Growth and Production of  Submerged Tolerant Rice Variety. JLSO 1(1):12-21.This study aimed at analyzing the effect of submergence and N fertilizer application on the plant growth and production of submergence tolerant rice variety. Problems and constrains of  rice production on flood prone and flash flood lowlandbecoming more frequents and more intens, causing submergence of the whole parts of rice crops for certain periods. The experiment was conducted to determine the effect of submergence and N fertilizer application on the growth of two treatment factors using block randomized design  with submergence tolerant variety Inpara 4 and 5.   An experiment was conducted in the greenhouse at Muara Experimental Station, Bogor in 2009. The treatments  consistedof three replications. The first factor was submergence rice variety Inpara 4 and 5 and the second factor was N management application, whereas (1) 200 kg Urea/ha, (2) 300 kg Urea/ha;  (3) 300 kg Ponska/ha + 100 kg Urea/ha; (4) 400 kg Ponska/ha (2x); (5) Briquette Urea  (300 kg Urea/ha) dan (6) 300 kg Urea/ha  +  Silikat (400 kg SiPPadi HS/ha).  Result of the experiment showed that   submergence for 14 to 24 DAP (10 days) on submergence tolerant rice variety combined with Briquette Urea (300 kg urea/ha  wrapped in strawpaper)  has increased the percentage of tiller number up to 98,9 percent , increased the highest total grain weight  for submergence tolerant rice  up to 41,2 gr per pot and increased in the proportion of  wet leave weight growth rate for  submersion treatment up to 1,4g per pot than that  without submergence.